A Study to Assess the Effectiveness of Osteoarthritic Nosode vs. Constitutional Medicine in the Management of Osteoarthritis of Knee Joint (Advancements in Homeopathic Research, 2022)
Osteoarthritis is an important cause of disability and the second most common musculoskeletal problem in the world (30%) after back pain (50%). The prevalence of osteoarthritis increases with age. An estimated 10% to 15% of all adults aged over 60 have some degree of OA, with prevalence higher among women than men.The reported prevalence of OA in rural India is 5.8%. Homeopathy offers a wider range of options than Conventional medicine. Conventional treatment consists of anti-inflammatory drugs and corticosteroids. Long term use of these medicines can cause plenty of side-effects. This study is to know the efficiency of homeopathic medicines in the cases of Osteoarthritis, and also to make a comparative analysis of osteoarthritic nosode & constitutional medicine in the management of osteoarthritis of knee joint.
Keywords: Homoeopathy; Osteoarthritis; Constitutional medicine; OA nosode; Knee joint